High-Dose Ipilimumab and High-Dose Interleukin-2 for Patients With Advanced Melanoma - Silk, Ann W.; Kaufman, Howard L.; Curti, Brendan; Mehnert, Janice M.; Margolin, Kim; McDermott, David; Clark, Joseph; Newman, Jenna; Bommareddy, Praveen K.; Denzin, Lisa; Najmi, Saltanat; Haider, Azra; et al. (Frontiers in Oncology, 2020)
High-dose ipilimumab (IPI) and high-dose interleukin-2 (IL-2) are approved agents for metastatic melanoma, but the efficacy and safety of the combination are unknown. The objective of this study was to evaluate the feasibility, safety, and efficacy of combination high-dose IPI and high-dose IL-2 in patients with histologically confirmed advanced unresectable stage III and IV melanoma. This Phase II, multicenter, open-label, single-arm trial was conducted in nine patients enrolled between 12/2014 and 12/2015. Subjects were treated with high-dose IPI 10 mg/kg intravenous (IV) every three weeks for four doses starting at week 1 and high-dose IL-2 (600,000 IU/kg IV bolus every eight hours for up to 14 doses) concurrently with IPI at weeks 4 and 7. After the first 12 weeks of combination therapy, maintenance IPI (10 mg/kg IV) monotherapy was administered every 12 weeks for up to one year. No patient had received prior PD-1 blockade, and only one received prior vemurafenib. Confirmed partial response was achieved in one (11%), stable disease in four (44%), and progressive disease in four (44%) of nine patients. Two patients achieved durable disease control of 44+ and 50+ months at the most recent follow-up without subsequent therapy. The median overall survival was not reached after a minimum 24 months of follow-up time. One-year and two-year survival rates were 89% and 67%, respectively. Seven patients (78%) experienced grade 3 or 4 adverse events related to the study therapy, three of which were attributed to both agents. One patient discontinued the treatment due to liver and kidney toxicity. While toxicity was significant, all events were reversible, and there was no treatment-related mortality. Although the sample size was limited, combination therapy with high-dose IPI and high-dose IL-2 was feasible and associated with clinical benefit. IL-2-based compounds in combination with CTLA-4 blockade should be studied in advanced melanoma patients who fail to benefit from first-line PD-1 blockade.